2003
DOI: 10.1046/j.1341-8076.2002.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoxia on the auditory system of goat fetuses during extrauterine incubation

Abstract: Although fetal compensatory reactions, such as increases in mean blood pressure and flow rate of carotid artery during hypoxia were recognized, elongation of latency, and decrement of amplitude were observed in the auditory brainstem response and middle latency response. These results suggest that hypoxia itself influences the auditory system of the fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…It is well known that hearing impairment occurs in the fetuses of pre‐eclamptic mothers . In one study that investigated the effect of hypoxia on the auditory system of goat fetuses during extrauterine incubation, it was found that hypoxia itself influences the auditory system of the fetus . However, the number of studies regarding cochlear function in patients with pre‐eclampsia is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that hearing impairment occurs in the fetuses of pre‐eclamptic mothers . In one study that investigated the effect of hypoxia on the auditory system of goat fetuses during extrauterine incubation, it was found that hypoxia itself influences the auditory system of the fetus . However, the number of studies regarding cochlear function in patients with pre‐eclampsia is limited.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] In one study that investigated the effect of hypoxia on the auditory system of goat fetuses during extrauterine incubation, it was found that hypoxia itself influences the auditory system of the fetus. 24 However, the number of studies regarding cochlear function in patients with preeclampsia is limited. Bakhshaee et al studied cochlear function in 37 patients with pre-eclampsia and 38 control subjects during pregnancy and the postpartum period (within 2 weeks), and they reported hearing impairment in five out of 37 (13.5%) patients during pregnancy.…”
Section: Figurementioning
confidence: 99%